UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA MELALUI METODE BUZZ GAMES - Faridatunnida, Faridatunnida; Tantowie, Tanto Aljauharie; Dudi, Dudi (Bestari, 2019)
The objectives of this study are as follows: (1) To find out the preparation of the Learning Implementation Plan (RPP) using the Buzz Games method in the Indonesian subjects of objects, animals and plants around me in the Madrasah Ibtidaiyah Darussalam. (2) To find out the implementation of learning by using the Buzz Games method in Indonesian subjects of objects, animals and plants around me in the Madrasah Ibtidaiyah Darussalam. (3) To find out the improvement of speaking skills from using the Buzz Games method in Indonesian subjects of objects, animals and plants around me in Madrasah Ibtidaiyah Darussalam. The method used is the Classroom Action Research (CAR) method of the Kemmis and MC Taggart models which are commonly used with 4 stages, namely: (1) planning, (2) implementation (3) observation and (4) reflection. After doing research, the results show that: (1) Teachers have increased their ability to prepare lesson plans. The average value in cycle I reached 8.7, cycle II reached 8.9 and cycle III reached 9.2. (2) The teacher experienced an increase in implementing learning with an average cycle I reaching 8.6, cycle II reaching 8.7 and cycle III reaching 9.1. (3) The assessment of students' speaking skills in class 1 / B MIS Al-Fadliliyah Darussalam Cijeunjing District Ciamis District has increased with an average value in cycle I reaching 6.87, cycle II reaching 7.08 and cycle III reaching 7.4. After using the buzz games method it can improve students' speaking skills.